Viscose Rayon Pulp from Blue Gum (Eucalyptus globulus Labill.) by Water-prehydrolysis Sulphate Process - Brat, R. V.; Singh, Man Mohan (Indian Forester, 1957)
A method for the preparation of viscose rayon grade pulp from blue gum wood has been worked out. Water-prehydrolysis sulphate process followed by muUltistage bleaching and refining has been used. The pulp was tested in Germany by a well-known viscose rayon pulp manufacturing firm and found to fulfil the conditions required for viscose rayon pulp.